Reading the Runes: Conflict, Culture and "Evidence" in Law-making in the UK. (1st April 2017) - Crewe, Emma
Abstract : In public discourse the idea of "evidence-based" law-making implies that expert opinion consists of incontrovertible facts that can be turned into solutions, irrespective of politics. Laws about children are often conceived as if they are especially free from the contamination by politics. This paper will challenge such assumptions, relying on a contemporary historical and ethnographic study to demonstrate how evidence and politics are entangled when you have conflicts over cultural change. I followed one clause about parenting as it made its journey through the Westminster Houses of Parliament to be transformed from a bill into the Children and Families Act 2014, observing the rituals of the chamber and committees, and the more discursive private discussions with civil society, which led to changes to the parliamentary texts. I found a complex web of relationships behind the public performances and underneath these texts and meetings between Ministers, civil servants, Parliamentarians, activists, lawyers, social workers, fathers, mothers and children. Making law is more about negotiating between clashing interests and values and reading the runes than weighing up evidence and planning the future as if it could be predicted.